2007
DOI: 10.1017/s1461145707007626
|View full text |Cite
|
Sign up to set email alerts
|

The role of oligodendrocyte pathology in schizophrenia

Abstract: Neuroimaging and microarray studies provide evidence for myelin and oligodendrocyte abnormalities in schizophrenia (SZ). Electron microscopy demonstrated dystrophy, necrosis and apoptosis of oligodendrocytes, the most severely affected cells in SZ. The proportion of myelinated fibres with atrophy of axon and swelling of periaxonal oligodendrocyte processes increased significantly in the prefrontal cortex (PFC), caudate nucleus and hippocampus in SZ compared to controls. Morphometry showed a deficit of oligoden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
95
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 55 publications
5
95
0
3
Order By: Relevance
“…35 However, there was no significant association between the cis SNPs and the expression level of the gene in the SNPExpress database, 24 and we were unable to confirm the SNP association in our samples, as the gene is absent from our expression microarray data set. Nevertheless, deficits in oligodendrocytes have been identified as a significant neuropathology in schizophrenia and in bipolar disorder, 36,37 and genome-wide expression profiling revealed that oligodendrocyte-related genes are downregulated in the PFC of both schizophrenia and bipolar disorder. [38][39][40] The findings from the genome-wide scan will need to be replicated by an independent association study with a larger sample size; however, the preliminary findings support the hypothesis that developmental deficits of oligodendrocytes may contribute to the etiology of major psychiatric disorders such as schizophrenia and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, there was no significant association between the cis SNPs and the expression level of the gene in the SNPExpress database, 24 and we were unable to confirm the SNP association in our samples, as the gene is absent from our expression microarray data set. Nevertheless, deficits in oligodendrocytes have been identified as a significant neuropathology in schizophrenia and in bipolar disorder, 36,37 and genome-wide expression profiling revealed that oligodendrocyte-related genes are downregulated in the PFC of both schizophrenia and bipolar disorder. [38][39][40] The findings from the genome-wide scan will need to be replicated by an independent association study with a larger sample size; however, the preliminary findings support the hypothesis that developmental deficits of oligodendrocytes may contribute to the etiology of major psychiatric disorders such as schizophrenia and bipolar disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Postmortem examination of schizophrenic brains has demonstrated structural abnormalities in both myelin sheaths and oligodendroglia and it has been hypothesized that oligodendroglial dysfunction induces abnormalities in myelin, thereby contributing to the disease etiology. [46][47][48] Alternatively, aberrant PI levels may influence vesicle trafficking and vesicle cycling, important determinants in neurotransmitter cycling. Hence, PI kinase genes (including PIK4CA, PIP5K2A and PIK3C2G) are functional candidates for contributing to the risk of developing schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…125 While many questions remain regarding the involvement of white matter loss in schizophrenia, OL apoptosis has been reported in schizophrenic brains. 126 It remains to be seen whether this is a cause or consequence of schizophrenia. 127 …”
Section: Ols and Diseasementioning
confidence: 99%